Study of a torsion spring fracture. (April 2019) - Valles González, María Pilar; García-Martínez, María; Pastor Muro, Ana
Abstract: One flange of a spring belonging to an actuator drive that worked under torsion has been fractured. It is placed next to the electric motors whose mission is to move the drive manually through a hexagonal key. The whole equipment is an extensor-retraction actuator consisting in two electric motors that run a gear. This gear pulls a chain moving a telescopic beam. It was confirmed that there was no signs of anomalous working previous to the fracture. Some roughness requirements were mandatory in the first wire of the spring as well as both spring flanges, thus two springs (used and new) were compared. Several tests were performed in order to determine the cause of the fracture such as a chemical and mechanical characterization of the material, a fractographic analysis of the fracture surface, and the determination of the spring treatment state using metallographic and microscopic techniques. Additional observations were carried out in the other flange in order to detect possible defects. It was verified that the material corresponds to a 300 maraging steel type IV in a solubilization and ageing heat treatment state. The fracture surface presented fractographic characteristics of a typical progressive fracture. It was concluded that although the steel type and treatment state is correct, the roughness of specific zones is not well finished and, may have generated a crack that have nucleated in a notch of the first wire of the spring inner side surface. The crack may be produced by a pinned particle or any other surface defect that afterwards may propagate by a fatigue mechanism. Highlights: The procedure to study the fracture of a spring flange is presented. A fractographic study, a microstructural characterization and roughness inspection were carried out. The fracture occurred by a fatigue mechanism whose origin was a surface defect.